The options of project financing and funding for retrofitting works as a hybrid approach (HA) on conserving the historical building in Malaysia - Kamarudin, Muhammad Khairi; Jaapar, Aini; Harun, Rosta; Yahya, Zaharah (American-Eurasian Network for Scientific Information (AENSI) Publications, 2015)
Retrofitting the historical buildings in Malaysia is considered new since the prominent retrofitted historical building was open to public in 2005. It is known as Kuala Lumpur Performing Art Centre (KLPac). The transformation gives new looks externally and internally to the buildings as well as additional of new spaces inside it apart from reusing back the original structures and façade accordingly. As result, retrofitting mechanism is considered as a Hybrid Approach (HA) in conservation works. Strong cash flow and funding is vital and the key essential to a successfully retrofitting historical buildings. Therefore the objective of this paper is to identify the project financing and funding options for retrofitting works on the historical buildings in Malaysia. Site visits, case studies, identification of retrofitted historical buildings, reviewing secondary data and one to one interviews were done for this research.